Implementation of the Hybrid Mobile Application in The Street Artist Painting Auction Application â€œStrauctionâ€ - Angga Cahya Abadi; Reichan Muhammad Maulana; Rizky Septiana Abdul Razak (International Journal of Research and Applied Technology (INJURATECH), 2023)
The works of street artists' paintings tend to have minimal interest in Indonesia. This is caused by many factors, one of which is the limited scope of painting marketing. Therefore, the author seeks to provide a means of marketing in the form of an online painting auction application. The purpose of this research is to create an application as a means of connecting painting artists with painting enthusiasts. The research method used is descriptive analysis method with a quantitative approach. While in the development process, this application adopts the Hybrid Mobile Application method which has many advantages over the Native Android and IOS methods. The advantages of this hybrid method are in terms of coding effectiveness and efficiency of time and resources used. By applying this method, the application can be accessed from various circulating smartphone operating systems such as Android and IOS so that it can make it easier for the application to be accessed by potential users. The main concept of this application is to implement an auction system in the sale of paintings. This application also has several core features such as painting auctions, homepage, explore, bidding, payments and other supporting features that are expected to facilitate the painting auction transaction process. In the end, this application is intended for painting artists and painting lovers so that it can be easier to make transactions for buying and selling paintings online.